An Orchestral Audience: Classical Music and Continued Patterns of Distinction. (December 2014) - Crawford, Garry; Gosling, Victoria; Bagnall, Gaynor; Light, Ben
This paper considers the key findings of a year-long collaborative research project focusing on the audience of the London Symphony Orchestra and their introduction of a new mobile telephone ('app') ticketing system. A mixed-method approach was employed, utilizing focus groups and questionnaires with over 80 participants, to research a sample group of university students. This research develops our understanding of classical music audiences, and highlights the continued individualistic, middle-class, and exclusionary culture of classical music attendance and patterns of behaviours. The research also suggests that a mobile phone app does prove a useful mechanism for selling discounted tickets, but shows little indication of being a useful means of expanding this audience beyond its traditional demographic.